Analysis of Shallot (Allium Ascalonicum L) Availability Fluctuation in the Yogyakarta Special Region - Pujo Saroyo; Savitri Mareta (Agroindustrial Journal, 2020)
Shallot is one of the food commodities that determine or influence the political policy inIndonesia. Shallot (Allium Ascalonicum L) is a horticultural commodity, the price of which oftenexperiences significant fluctuations in Yogyakarta Special Region. Shallot prices can increase ordecrease significantly in monthly or even weekly periode due to fluctuation of its availability. Theobjective of this research was to analyze the fluctuation of shallot availability in the specialregion of Yogyakarta. It was conducted through field survey and by collecting secondary data onshallot commodity in Special Region of Yogyakarta in 2017. To support data about shallotdeterioration rate during storing period, the research on how to store shallot was conducted in awarehouse owned by farmer group “Ngudi Makmur” in Samiran, Parangtritis Village, KretekDistrict, Bantul Regency. The results showed that the fluctuation of shallot availability inYogyakarta Special Region was caused by the decrease of shallot production in the mainproduction center of Bantul district which contributed about 70% from local production, thefluctuation of supply from the surrounding area that had the planting season and harvest seasonssimilar to those in Yogyakarta Special Region, the deterioration rate that was still high duringstoring period and the lack of significant role of BULOG in controlling the availability of shallotdue to limitations of its storage technology